2015
DOI: 10.1371/journal.pntd.0003394
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Salmonella Typhimurium ST313 with Naturally Attenuated Flagellin Elicits Reduced Inflammation and Replicates within Macrophages

Abstract: Invasive non-typhoidal Salmonella (iNTS) are an important cause of septicemia in children under the age of five years in sub-Saharan Africa. A novel genotype of Salmonella enterica subsp. enterica serovar Typhimurium (multi-locus sequence type [ST] 313) circulating in this geographic region is genetically different to from S. Typhimurium ST19 strains that are common throughout the rest of the world. S. Typhimurium ST313 strains have acquired pseudogenes and genetic deletions and appear to be evolving to become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 50 publications
10
89
0
Order By: Relevance
“…However, the pathogenicity of S. Typhimurium has recently been changing, with more invasive and multidrug-resistant strains being increasingly isolated from the blood of malnourished children and immunocompromised adults living in sub-Saharan Africa(111113). These newly emerging strains have developed an improved ability to replicate within human macrophages while down-regulating production of flagella to reduce innate immune recognition(114). With this unsettling rise in unconventional invasive non-typhoidal Salmonella (iNTS) strains, it may therefore be appropriate to revisit available attenuated S. Typhimurium vaccines with the goal of improving the safety of existing vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathogenicity of S. Typhimurium has recently been changing, with more invasive and multidrug-resistant strains being increasingly isolated from the blood of malnourished children and immunocompromised adults living in sub-Saharan Africa(111113). These newly emerging strains have developed an improved ability to replicate within human macrophages while down-regulating production of flagella to reduce innate immune recognition(114). With this unsettling rise in unconventional invasive non-typhoidal Salmonella (iNTS) strains, it may therefore be appropriate to revisit available attenuated S. Typhimurium vaccines with the goal of improving the safety of existing vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the S. Typhimurium vaccine is derived from a clinically relevant genotype that has been associated with invasive disease and is prevalent in sub-Saharan Africa. There are multiple genetic and phenotypic differences (22,23) between ST19 and ST313 strains, and a vaccine derived from a genotype that is circulating in the target population is likely to be most effective by affording cross-protection via shared antigens. However, one of the main reasons for developing an ST313-based vaccine is that these strains produce less enteropathogenicity than ST19 strains, which we anticipate will result in less inflammation and possibly reduced shedding (22).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to S. Typhimurium ST19 strains, the prototypic ST313 strain D23580 exhibits many pseudogenes and gene deletions (19). We and others have recently shown that S. Typhimurium ST313 is also phenotypically different from ST19 (21)(22)(23)(24). Despite observable differences between S. Typhimurium ST19 and ST313 isolates, it is also feasible that the morbidity and mortality associated with these strains in sub-Saharan Africa is due to other factors, such as comorbidities (e.g., malnutrition, HIV, and malaria), antibiotic resistance, or genetic predisposition (25).…”
mentioning
confidence: 99%
“…Typhimurium ST313 strains are phenotypically different from ST19 isolates (the most common genotype found throughout the world and which causes gastroenteritis). [87] S . Typhimurium ST313 isolates from sub-Saharan Africa are highly resistant to killing by macrophages and elicit reduced inflammation compared to S .…”
Section: Live Attenuated Vaccines Against Invasive Salmonella Seromentioning
confidence: 99%
“…Typhimurium ST19 isolates. [87] Carden et al have also shown that ST313 isolates produce less caspase 1 dependent macrophage cell death and IL-1β release compared to ST19 strains. [88] We anticipate that S .…”
Section: Live Attenuated Vaccines Against Invasive Salmonella Seromentioning
confidence: 99%